Dynamic versus Static Diagnostics - Jedličková, Petra; Sleziaková, Anna (Journal of Ecohumanism, 2025)
The presented article summarizes the importance of the dynamic diagnostic approach, which focuses on revealing the student’s potential and his ability to develop through interaction with the examiner of the diagnostic battery. Dynamic diagnostics does not look only at the current level, but follows the process and change in the student’s abilities and skills. Furthermore, it emphasizes the way in which the student comes to solving tasks and how his approach to them changes. It also takes into account the individual needs of the student, which can lead to a longer diagnostic process. Research has shown that students with ADHD/ADD have different performances in the test of distracted attention. We identified differences in their ability to internalize tasks in the speed and accuracy of work. This knowledge helps to better understand the individual needs of students and adapt the diagnostic process to support their learning and development.